The Use of Proprietary Biotechnology Research Inputs at Selected Latin American NAROs - Salazar, Silvia; Falconi, César A.; Komen, John; Cohen, Joel I. (International Service for National Agricultural Research, 2000)
During the past decade, the gradual globalization of the world’s economy—through the liberalization of markets and the institution of free trade agreements—has brought to the fore the topic of intellectual property rights (IPR). Indeed, in the changing environment of intellectual property protection, agricultural research organizations need to determine how, and under what conditions, new technologies or products can be acquired and to investigate whether and by what means they themselves can protect technologies and products. This Briefing Paper presents an assessment of the use of proprietary biotechnology inputs, and of prospects for generating innovative products from these, in the agricultural research systems of Brazil, Chile, Colombia, Costa Rica, and Mexico. The main findings of a survey conducted among 13 national agricultural research organizations (NAROs) in these countries led to the following recommendations: (1) to ensure the provision of a combination of legal, scientific, and technical guidance to help the NAROs address IPR concerns in a systematic way and in accordance with international policies, (2) to provide the NAROs with the specific regulations and policies they need, and (3) to take into account that there are academically oriented institutions and institutions with an applied orientation, when defining policies and scenarios for the NAROs.